2009
DOI: 10.1128/jcm.00566-09
|View full text |Cite
|
Sign up to set email alerts
|

Genes Related to Long Polar Fimbriae of Pathogenic Escherichia coli Strains as Reliable Markers To Identify Virulent Isolates

Abstract: Lpf (stands for long polar fimbriae) is one of the few adhesive factors of enterohemorrhagic Escherichia coli O157:H7 associated with colonization of the intestine. E. coli O157:H7 strains possess two lpf loci encoding highly regulated fimbrial structures. Database analysis of the genes encoding the major fimbrial subunits demonstrated that they are present in commensal as well as pathogenic (both intestinal and extraintestinal) E. coli strains and in Salmonella strains and that the lpfA1 and lpfA2 genes are h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
47
0
8

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 39 publications
(50 reference statements)
6
47
0
8
Order By: Relevance
“…The distribution of lpfA in tEPEC agreed with our previous study (26); however, this is the first description of isolates lpfA1-1 allele positive and lpfA2 negative in serotype O142:H34 (Table 4). From the 100 aEPEC strains analyzed, 41 lack both lpfA alleles.…”
supporting
confidence: 77%
See 3 more Smart Citations
“…The distribution of lpfA in tEPEC agreed with our previous study (26); however, this is the first description of isolates lpfA1-1 allele positive and lpfA2 negative in serotype O142:H34 (Table 4). From the 100 aEPEC strains analyzed, 41 lack both lpfA alleles.…”
supporting
confidence: 77%
“…Of the remaining 59 lpfA-positive strains, 20 contained the combination of lpfA1-2 and lpfA2-1 alleles. With the exception of one strain, all O55:H7 strains were lpfA1-3 and lpfA2-2, thus confirming previous findings with EHEC O157:H7 and LEE-negative STEC strains (10,26), that demonstrated that the presence of these two alleles is a reliable way to detect O157:H7 strains and the closely related O55:HϪ or O55:H7 serotypes. Although different combinations of these alleles were detected in aEPEC serotypes, we found that seven O119:H2 isolates carried the lpfA1-2 allele and were negative for lpfA2 (Table 3).…”
supporting
confidence: 76%
See 2 more Smart Citations
“…This process involves the recognition of receptor(s), located at the surface of the target cells, by adhesion factors expressed on the bacterial surface (23,35). To date, the intimin protein and the long polar fimbriae (Lpf) are the only two factors of EHEC that have been demonstrated to play a role in persistence and the colonization of the intestine (5,9,12,17,29,33). Further, the presence of intimin-negative EHEC strains that can cause severe disease in humans, including HUS (22), have led to the discovery of other putative adhesins (10, 15, 16, 20, 21, 24-26, 30, 31, 37, 39).…”
mentioning
confidence: 99%